Study of Drainage Channel Capacity in Tebalo, Gresik District - Dahliana Kurniawaty (Yayasan Ahmar Cendekia Indonesia, 2020)
The growth of Gresik City is shown by the development of various infrastructures such as settlements, highways, and others. Along with the growth of Gresik City area, an increase in flood inundation due to increasingly dense settlements, decrease of vacant land as an infiltration area in Tebalo Village. Flooding is caused due to lack of development of drainage systems in the area of Tebalo Village. To normalize Tebalo drainage channel, good planning must be prepared for Tebalo drainage channel system including planning the layout of the channel system, calculating the designed flood discharge for each channel, hydraulics analysis for flood flow conditions and also along high sea water tide conditions, and finally designing the dimensions of the channel. After the channel is normalized, it is expected that the flow would be much smoother so that no flooding occurs.